Good governance practices for waqf in Malaysian Higher Education Institutions (HEIs) - Hussin, Rohayati; Syed Abdul Kader, Sharifah Zubaidah; Manshor, Nurul Mazrah; Roslim, Salmah; Mohamad Sirat, Irinah (Allied Business Academies, 2021)
Many Higher Education Institutions (HEIs) in Malaysia have established waqf funds to generate and diversify their incomes. Good governance practices are recognized as a key success factor for the sustainability of waqf in HEIs. This paper provides an insight into the concept of good governance in HEIs and elaborates on several of its dimensions. Through intensive literature review as well as content analysis, it explains the concept of good governance and discusses how this concept could be practiced in sustaining waqf in HEIs. In summary, this paper adds value to the existing literature on governance as it explores the fundamental concepts for governance practices in waqf for HEIs. It is hoped that this paper will provide some requisite inputs towards improvement and efficient management of waqf in HEIs.